Mussel-inspired hybrid network hydrogel for continuous adhesion in water. Issue 10 (24th February 2020) - Fu, Yifu; Ren, Pengfei; Wang, Faming; Liang, Min; Hu, Wanjun; Zhou, Naizhen; Lu, Zuhong; Zhang, Tianzhu
Abstract : The mussel-inspired catechol-based strategy has been widely used in the development of adhesives. Abstract : The mussel-inspired catechol-based strategy has been widely used in the development of adhesives. However, the properties of the obtained adhesives were still severely limited in a humid environment, particularly in water. In this study, a facile and versatile approach was proposed to prepare an underwater adhesion hydrogel. First, dopamine (DA) was grafted on oxidized carboxymethylcellulose (OCMC) to obtain dopamine-grafted oxidized carboxymethylcellulose (OCMC-DA). Second, the acrylamide (AM) monomer was conjugated with OCMC-DA by a Schiff base reaction, and then polymerized to form an OCMC-DA/PAM hydrogel. The properties of the resulting hydrogel have been fully characterized. The underwater adhesion strength of the hydrogel can reach as high as 86.3 ± 7.2 kPa and reduced to 43 ± 3.4 kPa after being immersed in water for 9 days. More remarkably, we found that the maximal adhesion strength was shown when the G ′ and G ′′ of the hydrogel were very close. Moreover, we demonstrated the mechanical properties of our fabricated hydrogel by compressive tests and rheological analysis. The adhesive hydrogel also exhibits excellent biocompatibility.